Theoretical and Experimental Analysis of Concrete Stress-Strain with Artificial Coarse Aggregates and Steel Fibers - Meity Wulandari (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Artificial coarse aggregates is an innovation to replace natural coarse aggregate. In this study, the material used for the preparation of coarse aggregate is industrial waste, namely Expanded Polystyrene (EPS). The purpose of using this s in addition to knowing the magnitude of the compressive strength, it is also necessary to know the amount of strain that occurs when the concrete receives a load. In addition to improving the performance of compressive strength, steel fibers are also added to the concrete mixture. The method used in this research is experimental and analyzed with a mathematical model to determine the theoretical modeling of the stress-strain curve. The experimental test results show that the use of steel fibers can increase the compressive strength of normal concrete while the effect of this artificial coarse aggregates can increase the strain value by 39% of normal concrete. The results of experimental and theoretical comparisons of mixture composition which are considered to be closest to the stress-strain curve of normal concrete are concrete with a mixture of 15% artificial coarse aggregates and concrete with a mixture of 15% artificial coarse aggregates and 0,75% steel fibers.